Reinforcement design using geosynthetics for foundations with probability of dolinamento: Analytical calculation and numerical stress-strain model - Castro , Paulo Victor Silva Avelino de; Silva, Isabelle Tanne Couto e; Martins, Paula Mello (Seven Editora, 2023)
Karst zones are defined by their high solubility, porosity and consequence of subsidence occurrences. Considering that about 20% of of ice-free land is made up of karst regions, the present work aimed to reinforce by geosynthetics a hypothetical foundation subject to windings through the analytical methodology of Briançon and Villard (2007) and by modeling numerical stress-strain in RS2 software (Rocscience). Initially, a hypothetical foundation to be strengthened was defined, in which there is the presence of circular dolines of a maximum of 3 meters in diameter. For the determination of the mechanical properties of the reinforcement, the methodology proposed by Briançon and Villard (2007) was applied, having as a premise a surface deformation of, at most, 5%, whose results generated dimensioning abacuses to define the length parameters anchoring and traction effort of the geogrid. Numerical analyzes of the stress-strain type were performed to verify the level of strain related to the resistance of the foundation materials, considering the values obtained by the analytical method. The reinforcement by a geogrid set, for reinforcement and a woven geotextile, for physical separation, in elastoplastic regime, obtained resistance reduction factors (SRF) corresponding to the maximum surface deformations of 5%. The SRF obtained was consistent with good practices. It was observed that the deformations caused in the geosynthetics did not lead to their rupture. DOI:https://doi.org/10.56238/chaandieducasc-036